Error in Vowel Pronunciation Made by Informatics Students - nurul frijuniarsi (Scope : Journal of English Language Teaching, 2018)
The purpose of this study is to figure out the dominant factor causing the errors of vowels pronounced by second-semester students of Informatics which is basically nonnative speakers of English. The approach applied in this study is qualitative. The data were collected via observation and recording which were constructed in the form of field-notes then analyzed and measured in accordance to English phonetic transcription in “English Pronouncing Dictionary” written by Jones (1997).  This study involved 40 students of Informatics English subject at Informatics Program of Indraprasta PGRI University where English is only supporting subject. The data shows that the respondents were really lack of English pronouncing skill, especially vowels as 42 of 58 words containing vowels are pronounced incorrectly. As the result of study, we can conclude that the dominant error made by students is Interlingual errors (58,6% or 838 of 1.430 errors made by students), the errors occurred due to the interference of students? native language.